Montage, découpage, mise en scène essays on film form - Le Forestier, Laurent 1970-; Barnard, Timothy 1958-; Kessler, Frank 1957- (Caboose, 2020)
"This book consists of three essays about three aspects of aesthetics in the cinema: montage, découpage and mise en scène. The three authors, each taking one of these three topics, present a historical and theoretical overview of these concepts in film theory and practice and discuss how the three interrelate."--
Keywords: Filmästhetik; Motion pictures / Aesthetics; Motion pictures / Technique